2015
DOI: 10.1021/acs.jafc.5b00672
|View full text |Cite
|
Sign up to set email alerts
|

β-Cyclodextrin-Assisted Extraction of Polyphenols from Vine Shoot Cultivars

Abstract: This work optimized the β-cyclodextrin (β-CD)-assisted extraction process of polyphenols from vine shoots. The efficiency of β-CD was compared to that of ethanol in terms of the quantity and antioxidant capacity (AC) of the extracted polyphenols. Response surface methodology permitted the optimization of the β-CD concentration, time, and temperature. The optimal polyphenol content (PC) [5.8 mg of gallic acid equivalent (GAE)/g of dry matter (DM)] and AC [3146 micromolar trolox equivalent per milliliter (μMTE)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(28 citation statements)
references
References 21 publications
(32 reference statements)
1
27
0
Order By: Relevance
“…As the treatment time increased to 120 min, the recovered EGCG and ECG were declined to 91.1 mg/g and 35.6 mg/g, respectively. This might be due to the oxidation phenomenon that was likely to occur when subjecting phenolic compounds to high temperature for long durations (Palma and others ; Rajha and others ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the treatment time increased to 120 min, the recovered EGCG and ECG were declined to 91.1 mg/g and 35.6 mg/g, respectively. This might be due to the oxidation phenomenon that was likely to occur when subjecting phenolic compounds to high temperature for long durations (Palma and others ; Rajha and others ).…”
Section: Resultsmentioning
confidence: 99%
“…β‐CD has been generally recognized as safe by the Food and Drug Administration in 1998 and it is now extensively used as a flavor carrier and protectant in the food industry (Szente and Szejtli ). Recently, several researchers have reported that β‐CD can be used to extract polyphenols from grape pomace, apple pomace, vine shoot cultivars and Polygonum cuspidatum (Mantegna and others ; Ratnasooriya and Rupasinghe ; Rajha and others ; López‐Miranda and others ). Compared to organic solvents, β‐CD‐assisted extraction is more economic, safe, and green.…”
Section: Introductionmentioning
confidence: 99%
“…After an incubation of 30 min at room temperature, the absorbance was measured at 515 nm. The DPPH value of the extracts was expressed in micromolar Trolox equivalent per milliliter (μMTE; Rajha and others ).…”
Section: Methodsmentioning
confidence: 99%
“…Aqueous solutions of β-CD have been successfully used to assist polyphenol extraction from various matrices, including pomegranate [30], tea leaves [31], vine shoots [32] and Polygonum cuspidatum [33], but combination of β-CD with DES has never been reported. In the view of clarifying whether such a combination could boost polyphenol extraction yield, extractions with the DES tested were also performed in the presence of 1.5% (w/v) β-CD.…”
Section: The Effect Of β-Cyclodextrin (β-Cd) Additionmentioning
confidence: 99%